The Fund's Transparency Policy : Issues and Next Steps. (Policy Papers; Policy Paper ;, 2003)
This paper presents for consideration by Directors the issue of a move to a policy of presumed publication of staff reports, and lays out possible options for modalities of implementing the policy of presumed publication. The paper also addresses several issues deferred to this review including: (i) presumed publication of UFR staff reports in exceptional access cases; (ii) deletions of highly politically-sensitive information; (iii) presumed publication of Financial System Stability Assessment (FSSA) reports and a policy for publication of Technical Notes prepared in the context of the Financial Sector Assessment Program (FSAP); and (iv) presumed publication of Reports on the Observance of Standards and Codes (ROSCs). The paper also addresses the issue of a modification policy for staff policy papers prior to publication, and the possibility of withholding publication of a staff report when deletions of highly market sensitive material would significantly alter its key messages.